Vitamin D and cognitive function - Soni, Maya; Kos, Katarina; Lang, Iain A.; Jones, Kerry; Melzer, David; Llewellyn, David J. (Scandinavian journal of clinical & laboratory investigation. Supplement, 2012)
Abstract The role of vitamin D in skeletal health is well established, but more recent findings have also linked vitamin D deficiency to a range of non-skeletal conditions such as cardiovascular disease, cancer, stroke and metabolic disorders including diabetes. Cognitive impairment and dementia must now be added this list. Vitamin D receptors are widespread in brain tissue, and vitamin D's biologically active form [1,25(OH)2D3] has shown neuroprotective effects including the clearance of amyloid plaques, a hallmark of Alzheimer's Disease. Associations have been noted between low 25-hydroxyvitamin D [25(OH)D] and Alzheimer's disease and dementia in both Europe and the US. Similarly, the risk of cognitive impairment was up to four times greater in the severely deficient elders (25(OH)D < 25 nmol/L) in comparison with individuals with adequate levels (≥ 75 nmol/L). Further studies have also shown associations between low 25(OH)D concentrations and cerebrovascular events such as large vessel infarcts, risk of cerebrovascular accident and fatal stroke. Cross-sectional studies cannot establish temporal relationships because cognitive decline and the onset of dementia itself may influence vitamin D concentrations through behavioural and dietary changes. However, two large prospective studies recently indicated that low vitamin D concentrations may increase the risk of cognitive decline. Large, well designed randomized controlled trials are now needed to determine whether vitamin D supplementation is effective at preventing or treating Alzheimer's disease and dementia.